Carbon‐Doped Boron Nitride Nanosheets with Ferromagnetism above Room Temperature. (22nd July 2014) - Zhao, Chong; Xu, Zhi; Wang, Hao; Wei, Jiake; Wang, Wenlong; Bai, Xuedong; Wang, Enge
<x xml:space="preserve">Abstract</x> The possibility to induce magnetism in light‐element materials that contain only s and p electrons is of fundamental and practical importance. Here, weak high‐temperature ferromagnetism is observed in carbon‐doped boron nitride (B‐C‐N) nanosheets. The bulk‐quantities of B‐C‐N nanosheets that are free of metallic impurities are prepared through a multi‐step process. These B‐C‐N samples exhibit ferromagnetic hysteresis stable at room temperature and above, with saturation magnetization and coercivity comparable to the previously reported results of defective graphite samples. The ferromagnetic response disappears upon the removal of carbon dopants from the BN lattice, indicating that the observed magnetism originates from substitutional carbon‐doping rather than from extrinsic magnetic impurities. On the basis of first‐principle calculations it is shown that not only substitutional carbon doping in a honeycomb BN lattice favors spontaneous spin polarization and local moment formation, but also that the spin moments can exhibit long‐range magnetic ordering.